1994
DOI: 10.1213/00000539-199412000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Polyhalogenated and Perfluorinated Compounds that Disobey the Meyer-Overton Hypothesis

Abstract: Fourteen polyhalogenated, completely halogenated (perhalogenated), or perfluorinated compounds were examined for their anesthetic effects in rats. Anesthetic potency or minimum alveolar anesthetic concentration (MAC) was quantified using response/nonresponse to electrical stimulation of the tail as the end-point. For compounds that produced excitable behavior, and/or did not produce anesthesia when given alone, we determined MAC by additivity studies with desflurane. Nine of 14 compounds had measurable MAC val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
138
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(142 citation statements)
references
References 0 publications
4
138
0
Order By: Relevance
“…... , 100- Figure 4a illustrates the effects on homomeric glycine receptor of two novel halogenated compounds: 1-chloro-1,2,2-trifluorocyclobutane (F3) and 1,2-dichlorohexafluorocyclobutane (F6). Both compounds have a high lipid solubility, and the Meyer-Overton rule predicts that both should act as anaesthetics in vivo (Meyer, 1899;Overton, 1901;Koblin et al, 1994). However, only F3 is an anaesthetic and a comparison of the effects of these compounds may be useful in testing candidate sites of anaesthetic action (Mihic et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…... , 100- Figure 4a illustrates the effects on homomeric glycine receptor of two novel halogenated compounds: 1-chloro-1,2,2-trifluorocyclobutane (F3) and 1,2-dichlorohexafluorocyclobutane (F6). Both compounds have a high lipid solubility, and the Meyer-Overton rule predicts that both should act as anaesthetics in vivo (Meyer, 1899;Overton, 1901;Koblin et al, 1994). However, only F3 is an anaesthetic and a comparison of the effects of these compounds may be useful in testing candidate sites of anaesthetic action (Mihic et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…To define better the actions of alcohols and anaesthetics on glycine receptors, we tested a series of n-alcohols, including long-chain alcohols that produce anaesthesia in vivo and show a 'cut-off' for effects on ligand-gated ion channels (Dildy-Mayfield et al, 1996). We also tested several clinically useful anaesthetics as well as two novel compounds which are structurally related, but only one of which produces anaesthesia (Koblin et al, 1994;Mihic et al, 1994). In order to examine the actions of different alcohols and anaesthetics in both al and a 2 glycine receptors, we used the Xenopus oocyte expression system.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a cutoff effect was evident when a homologous series of n-alkanols (or n-alkanes) was tested with increasing anesthetic activity being observed up to a discrete alcohol size after which it disappeared even though the larger ineffective molecules were highly lipophilic (16). Finally, compounds that possess high lipid solubility and fail to display anesthetic activity regardless of their size have been described in obvious discordance with the central tenet of the lipid theory (28).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional dogma used to explain the mechanisms of action of volatile anesthetics has been that these compounds act 'non-specifically', perhaps by perturbing the properties of membrane lipids (reviewed by Franks and Lieb, 1994). However, research within the last several decades has demonstrated numerous inconsistencies between experimental observations and non-specific theories of general anesthesia (Franks and Lieb, 1994;Koblin et al, 1994;Krasowski and Harrison, 1999). A major problem with the non-specific theories is that some chemical compounds predicted to be anesthetics based upon their lipophilicity do not in fact produce anesthesia (Koblin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, research within the last several decades has demonstrated numerous inconsistencies between experimental observations and non-specific theories of general anesthesia (Franks and Lieb, 1994;Koblin et al, 1994;Krasowski and Harrison, 1999). A major problem with the non-specific theories is that some chemical compounds predicted to be anesthetics based upon their lipophilicity do not in fact produce anesthesia (Koblin et al, 1994). These compounds, originally called 'nonanesthetics', are now more properly referred to as 'nonimmobilizers'.…”
Section: Introductionmentioning
confidence: 99%